2021
DOI: 10.1183/23120541.00731-2020
|View full text |Cite
|
Sign up to set email alerts
|

Lumacaftor/ivacaftor changes the lung microbiome and metabolome in cystic fibrosis patients

Abstract: RationaleTargeted cystic fibrosis (CF) therapy with lumacaftor/ivacaftor partly restores chloride channel function and improves epithelial fluid transport in the airways. Consequently, changes in the microbiome that is adapted to CF lungs may occur.ObjectivesTo investigate the effects of lumacaftor/ivacaftor on respiratory microbial composition and microbial metabolic activity by repeatedly sampling the lower respiratory tract.MethodsThis was a single-center longitudinal observational cohort study in adult CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Moreover, a study following up CF patients for 6 years after IVA initiation has demonstrated that the bacterial burden, assessed through cultural methods, remained stable at the pre-treatment levels for all the observation periods [ 75 ]. The addition of CFTR correctors such as LUMA has shown an increase in microbial diversity in the CF airways in some studies [ 76 ] but other studies show a less marked response [ 77 ]. Neerincx et al [ 77 ] showed that in CF patients homozygous for the F508del CFTR mutation, treatment with LUMA/IVA for 6 months induced a temporary and moderate change in the lung microbiome mainly characterised by a reduction in the relative abundance of P. aeruginosa .…”
Section: Cftr Modulators and Cf Microbiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, a study following up CF patients for 6 years after IVA initiation has demonstrated that the bacterial burden, assessed through cultural methods, remained stable at the pre-treatment levels for all the observation periods [ 75 ]. The addition of CFTR correctors such as LUMA has shown an increase in microbial diversity in the CF airways in some studies [ 76 ] but other studies show a less marked response [ 77 ]. Neerincx et al [ 77 ] showed that in CF patients homozygous for the F508del CFTR mutation, treatment with LUMA/IVA for 6 months induced a temporary and moderate change in the lung microbiome mainly characterised by a reduction in the relative abundance of P. aeruginosa .…”
Section: Cftr Modulators and Cf Microbiologymentioning
confidence: 99%
“…The addition of CFTR correctors such as LUMA has shown an increase in microbial diversity in the CF airways in some studies [ 76 ] but other studies show a less marked response [ 77 ]. Neerincx et al [ 77 ] showed that in CF patients homozygous for the F508del CFTR mutation, treatment with LUMA/IVA for 6 months induced a temporary and moderate change in the lung microbiome mainly characterised by a reduction in the relative abundance of P. aeruginosa . A similar trend was observed in sputum metabolome, in particular for metabolites from the tryptophan–kynurenic acid pathway that seems to be related to the abundance of P. aeruginosa .…”
Section: Cftr Modulators and Cf Microbiologymentioning
confidence: 99%
See 2 more Smart Citations
“…These findings, in combination with volatile metabolite profiles associated with common CF pathogens and the host's immune response to infection, suggest that changes to the volatile metabolome during an exacerbation correlate with changes to the microbiome [49]. Similarly, a study combining metagenomics with two types of untargeted metabolomics analyses applied to sputum samples indicated that the temporary and moderate changes to the lung microbiome observed after initiating the CFTR modulating treatment Ivacaftor/Lumacaftor are mainly characterised by a reduction in the relative abundance of P. aeruginosa [50]. A branch of metabolomics dedicated to lipid analysis [51] (lipidomics) studies the lipids present in a sample, arising from host cells and tissues/lipid substrates [52].…”
Section: Metabolomics Profiling Of Cf Microbiotamentioning
confidence: 99%